Digital Comic Development for Elementary Social Studies Learning Outcomes: Pengembangan Komik Digital untuk Hasil Pembelajaran Mata Pelajaran Sosial di Sekolah Dasar - Hanum, Hilda Halimah; Rezania, Vanda (Indonesian Journal of Education Methods Development, 2025)
General Background: The integration of digital learning media in elementary education has become increasingly important to address students’ low motivation and limited engagement in Social Studies learning. Specific Background: Digital comics represent a visual and narrative-based instructional medium that aligns with students’ developmental characteristics and curriculum demands. Knowledge Gap: Although prior studies have discussed comic-based learning media, limited research has systematically developed and validated digital comics tailored to Social Studies content at the elementary level using a structured research and development framework. Aims: This study aims to develop and evaluate the feasibility and learning outcomes of a digital comic for fourth-grade Social Studies. Results: The product underwent expert validation, practicality testing, and implementation in classroom settings, demonstrating high validity and positive student responses, as well as measurable improvement in learning outcomes based on N-Gain analysis. Novelty: The study offers a structured digital comic design integrated with contextual content and validated through empirical classroom testing. Implications: The findings support the use of digital comics as an alternative instructional medium to support active learning and measurable academic improvement in elementary Social Studies. Keywords: Digital Comic, Social Studies Education, Learning Outcomes, Elementary School, Research And Development Key Findings Highlights: The developed product achieved high expert validation scores. Classroom implementation showed measurable score progression. Students demonstrated positive engagement toward the visual narrative material.